An assessment of factors influencing awareness, access and use of agro-climate services among farmers in Clarendon, Jamaica. Issue 126 (November 2021) - Fay Buckland, Sarah; Campbell, Donovan
Highlights: Climate Information Service (CIS) uptake is uneven across agro-climatic zones. Online agro-climatic information are least accessible to farmers. Age, extension support, and institution membership influence access to CI. Use of CIS is shaped by gender, climate perception and agronomic factors. Co-design of CIS can enhance uptake and diffusion. Abstract: In recent times, the provision of agro-climate services has been elevated as an adaptation policy priority across the Caribbean. Despite strides in such efforts, there is a paucity of research on levels of awareness and use of climate services by farmers. Understanding these nuances can illuminate important pathways for improving climate service uptake and delivery for favourable social and economic development outcomes. In this paper, we used a mixed-method approach to assess the factors influencing climate service uptake among farmers (N = 356) in one of Jamaica's principal agricultural regions, Clarendon. Regression analysis techniques were used to specifically determine the likelihood of farmers' awareness, access and use of locally developed climate services disseminated via TV/radio, climate text message, online farmer bulletin, and community-specific forecast across fifteen (15) social and environmental variables. Eight (8) factors were found to have significant influence on climate service awareness, access, and use (p < 0.05). These include gender, age, access to extension service, participation in groups/organizations, climate change perceptions, non-farm income, farm size, and agronomic conditions. The active use of the climate and weather information was closely linked to farmers' experiential observation of the relevance of the information within their own immediate context. Qualitative case study analyses further highlighted socio-spatial patterns of inequalities in CIS use, being dominated by the younger, more educated demographic. These results highlight potential entry points for increased tailoring of the design and delivery of agro-climate service products for greater effectiveness in climate service delivery. Given the projected impacts of increased climate variability on Caribbean agricultural systems, learning how farmers interact with agro-climate service products can surface opportunities to increase uptake and strengthen resilience.